ACUTE URINARY INFECTIONS AMONG CHILDREN AND THEIR ANTIBACTERIAL THERAPY - I.L. Chashchina; L.K. Katosova; A.M. Fedorov (Педиатрическая фармакология, 2006)
The article highlights the findings as to the peculiarities of clinical manifestations and diagnostics of urinary infection in childhood. The researchers provide the information on the urinary infection agent structure and e. coli resistance frequency (most widely spread agent) towards the antibacterial medications. They have also offered recommendations for rational antibiotic therapy.Key words: urinary infection, children, e. coli, cephalosporin of iii generation, ceftibuten.